John Gower’s Iberian footprint: the manuscripts - Yeager, R. F. (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
The English poet John Gower (d. 1408), unlike his close friend Geoff rey Chaucer, seems never to have visited Spain. Yet it is Gower’s great poem Confessio Amantis, and no work of Chaucer’s (or of any other English writer for two centuries more) that was translated into not one, but two, Iberian languages—and very likely during the poet’s lifetime. The evidence for Gower’s “footprint” is the presence of two fifteenth-century manuscripts, one Portuguese and one Castilian, now in the collections of, respectively, the libraries of the royal palace in Madrid, and El Escorial. Somewhat surprisingly, these manuscripts have been little discussed by either Spanish- or English-speaking scholars. Even from among those who know of their existence—a relatively small number, compared to the many who read and teach Gower’s work—one would be hard put to name more than a halfdozen who have even viewed them, let alone studied them with any systematic care. The paper has two parts: fi rst, a brief physical description of each manuscript; second, some conclusions that the physical elements of the manuscripts, and their idiosyncratic content, suggest about the probable identities of the Castilian and Portuguese patrons of the translations, and their likely motivations for having the translations made. Keywords: John Gower, Confessio Amantis, Cinkante Balades, Escorial MS g.II.19, Confi syión del Amante, Juan de Cuenca, Huete, MS Real Biblioteca II-3088, Livro do amante, João Barroso, Ceuta, John of Gaunt, Philippa of Lancaster and Portugal, Katherine of Lancaster and (Catalina) of Castile, João I, Henry (Enrique) III of Castile, Roberto Paym (Robert Payne), Dom Duarte I, Leal Conselheiro, Christine de Pizan, Henry IV of England, Henry V of England, L’Avision de Christine.